2022
DOI: 10.1007/s10882-022-09853-w
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Exploring Parental Perceptions of Telehealth in Early Intervention

Abstract: Using telehealth as a mode of service delivery has the potential to address some long-standing challenges in early intervention (EI) services such as waiting lists to access services. Yet, little is known about parent perceptions of telehealth in EI based on their lived experiences partnering with EI practitioners. The purpose of this study was to explore parent perceptions on using telehealth, especially on family-professional partnerships and coaching. Interviews were conducted with 15 parents of children re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…On the other hand, the results obtained in the study by Cheung et al [ 54 ] point to the need for practitioners to strengthen their knowledge and skills to provide a service based on the family-centered model. The ultimate goal is to empower caregivers by creating learning opportunities for this learning to be generalized and applied to the natural environment [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results obtained in the study by Cheung et al [ 54 ] point to the need for practitioners to strengthen their knowledge and skills to provide a service based on the family-centered model. The ultimate goal is to empower caregivers by creating learning opportunities for this learning to be generalized and applied to the natural environment [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research continues this line of prevention and intervention in determining aspects of the health of infants aged 0 to 6 years, showing rates of effectiveness and acceptability, in which the figure of the family and its context are highlighted in the process [ 42 , 45 , 51 , 53 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…; Cheung, Aleman-Tovar et al, 2022), aspects of virtual learning that are critical when engaging in motor activities. Besides access to devices, it may be helpful to have initial in-person visits if there are no prevailing health concerns, to troubleshoot technical issues such as camera position, adequacy of internet speed, compatibility of hardware (e.g., headphones) and software, assurance of direct and stable internet connections (Cheung, Aleman-Tovar et al, 2022;Lerman et al, 2020), and access to sufficient space for children to safely engage in motor play. Notably, such visits should be individualized to meet each family's needs (Fraser et al, 2017).…”
Section: Logistical Issuesmentioning
confidence: 99%
“…It has been used in a variety of ways such as for recording/watching videos, delivering remote services, and sharing information. Challenges are related to accessing technology (e.g., devices, internet) and families’ understanding of their role during remote services (i.e., telepractice) (Cheung et al, 2023; Chung et al, 2020; Marturana & Woods, 2012; Meadan et al, 2020; Yang et al, 2021). However, when access to stable and reliable technology is available and EIs and families understand how to use technology, it can address some barriers to coaching.…”
mentioning
confidence: 99%
“…However, when access to stable and reliable technology is available and EIs and families understand how to use technology, it can address some barriers to coaching. For example, families perceived telepractice as advantageous because it enabled flexible scheduling, family engagement, communication, coaching, and access to more families (Cheung et al, 2023; Yang et al, 2021). Researchers suggested that it may be difficult to coach caregivers due to the limited time allocated to in-person visits; however, using technology to share videos for reflection and feedback between sessions addresses these time constraints (Meadan et al, 2018).…”
mentioning
confidence: 99%